A disclosure framework to enhance accountability and transparency for public-private partnership (PPP) in Egypt: with a case study - Mustafa, Samih Abd al-Salam; Husayn, Amal Husayn Muhammad (المجلة العلمية للدراسات و البحوث المالية و التجارية : علمية محكمة., 2023)
Purpose: while PPP have been widely researched in many aspects, private partner disclosure of PPP information has not been addressed. this study aims to provide a comprehensive framework for the disclosure of information on PPP projects in Egypt, to contribute to filling some gaps in research, and to enhance accountability for PPP projects in Egypt. design / methodology / approach: the disclosure framework is designed based on the main drivers for disclosure, the main factors that are directly related to the disclosure requirements under the Egyptian accounting standard (EAS) no. 44 disclosure of interests in other entities, and the different uses and categories of information users. with a focus on the utilities sector in Egypt, a case study approach was used to implement the disclosure framework. research limitations: although all the elements of disclosure are very important, researchers have focused their attention on those elements that deserve more attention from the point of view of the PPP and related to disclosure requirements under EAS 44. originality / value: the main contributions made by this paper relate to achieving compliance with disclosure requirements under EAS 44 in the proposed framework, as well as providing important insights for fruitful directions that future research can take to investigate the extent and quality of disclosure by private sector partners. تسعى الحكومات إلى تعزيز فرص الاستفادة من إمكانيات القطاع الخاص الإدارية والتمويلية والتقنية في إنشاء وتطوير وتوسيع وتشغيل وصيانة أصول البنية التحتية وتقديم الخدمات العامة في العديد من القطاعات كالطاقة والمياه والصرف الصحي، والاتصالات والنقل، وغيرها، من أجل التغلب على تحديات توفير التمويل اللازم للإنفاق الحكومي لتلبية الطلب المتزايد على الخدمات والمرافق العامة. وفي إطار توفير بيئة داعمة لتنفيذ شراكات استراتيجية ناجحة مع القطاع الخاص في مصر؛ استهدفت الدراسة تعزيز الأطر التنظيمية والمؤسسية للشراكات بتقديم إطارا شاملا للإفصاح عن مشروعات الشراكة من أجل تعزيز الإفصاح والمساءلة والشفافية للقطاع الخاص. تم تصميم الإطار المقترح بناء على الدوافع العامة للإفصاح، ومتطلبات الإفصاح الرئيسة الواردة في معيار المحاسبة المصري رقم 44 بعنوان "الإفصاح عن الحصص في المنشآت الأخرى". واستخدام الباحثان منهج دراسة الحالة لتطبيق الإطار المقترح على مشروع محطة القاهرة الجديدة للصرف الصحي بمدينة القاهرة الجديدة، أحد مشروعات قطاع المرافق العامة في مصر، كدراسة حالة. وتتمثل المساهمات الرئيسة لهذه الدراسة في تعزيز الشفافية والإفصاح والمساءلة من قبل شركات القطاع الخاص، وتحقيق الامتثال لمتطلبات معيار المحاسبة المصري رقم 44، فضلا عن توفير إطار شامل للإفصاح يمكن للبحوث المستقبلية الاعتماد عليه لاختبار مدى وجودة الإفصاح من قبل القطاع الخاص.